Rancang Bangun Content Management System Untuk Situs Web Instansi Pemerintahan - Azmi Inda Roby; Rinda Cahyana; Rina Kurniawati; Leni Fitriani (Institut Teknologi Garut, 2022)
Currently, information media that can be accessed online is very much needed to find out information quickly and can be accessed anywhere as long as there is internet access. Based on the regulation of the President of the Republic of Indonesia Number 54 articles 2 and 3 of 2015 concerning the Ministry of Communication and Information, it is stated that the Office of Communication and Information is a regional apparatus that handles the field of information to be disseminated to the public in the work area. There are about 42 sub-districts, 422 villages and 21 sub-districts in the Garut Regency area, but according to the Head of the Application Development Section for the Garut Regency Communication and Information Office, many regional officials do not yet have information dissemination facilities in the form of a website. By using a Content Management System, government agencies will be able to easily provide information and services to the general public as well as provide solutions for implementing the Public Information Disclosure Act. government that does not yet have an official website. The methodology used is the Rational Unified Process as one of the stages of developing an interactive system specifically for object-oriented programming and using the Black-box testing method as application testing later. The results of this study are a Content Management System application that can be used as an official website by government agencies for the purpose of delivering information to the public.